Analisis Gaya Kepemimpinan Manajer Internasional (Jepang) Dan Manajer Nasional (Indonesia) Pada Departemen Steel PT. Hanwa Indonesia - Priyanka, Ellissa; Raharja, Sam’un Jaja; Muftiadi, Anang (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
Every leader in an organization has a different leadership style based on background and cultural beliefs which will determine the effectiveness of an organization. Therefore, this research aims to analyze the leadership styles of international managers (Japan) and national managers (Indonesia) in the Steel Department of PT. Hanwa Indonesia along with related factors, obstacles and opportunities encountered by each leader as well as how each leader faces obstacles and opportunities and makes adjustments to achieve company goals. This research uses a qualitative research method with data collection techniques through related literature and interviews with the resource person, one senior manager of the PT Steel Department. Hanwa Indonesia who comes from Japan and one manager who comes from Indonesia as well as several local employees who have worked for more than three years. The data analysis technique uses data validity and reliability methods which are tested through a triangulation process. The results of this research show that the leadership styles of international managers (Japan) and national managers (Indonesia) in the Steel Department of PT. Hanwa Indonesia is a democratic leadership style that is supported by the ability to learn from the experience and interpersonal skills of each leader and the cultural values and traditions of Japan and Indonesia. Obstacles in leading lie in differences in cultural backgrounds involving language and habits. Therefore, each leader seeks to develop cultural sensitivity by learning and understanding their respective language and culture and using their interpersonal skills to guide and facilitate change efforts. Â